A lifespan perspective on decision-making: A cross-sectional comparison of middle childhood, young adulthood, and older adulthood - Stefanie Lindow; Anna Lang (Journal of Behavioral Decision Making, 2021)
Study 1 contributes to the sparse empirical research on decision-making across the lifespan by presenting a direct comparison of middle-aged children's (N0.167em=0.167em40; fourth grade), younger adults' (N0.167em=0.167em40; 20–390.167emyears), and older adults' (N0.167em=0.167em40; 62–820.167emyears) adaptive decision-making. Participants played a non-probabilistic, multi-attribute, information-board decision game and completed a verbal skill test (serving as an indicator of crystallized intelligence). Information search and choices were analyzed for two task structures (manipulated within-subjects; few vs. many relevant information-dimensions). The competence to adapt search to the task structure was found from middle childhood to older adulthood. Also, participants of all age groups made comparably good, informed choices. Thus, results highlight similarities in decision-making across a wide age range. Still, we observed distinct patterns on the process level. Older adults demonstrated difficulty in ignoring irrelevant information and searched an overly extensive information subset. In contrast, children showed an information-frugal approach that was widely similar to younger adults. A reanalysis of Study 1's data and previous studies (N0.167em=0.167em228) expands the child sample from third to sixth grade. It supports our main findings and suggests developmental improvement across childhood. In Study 2, we used a metacognition questionnaire to investigate the role of crystalized intelligence that might be a compensation mechanism for older adults (N0.167em=0.167em63). We discuss implications for adaptive decision-making models.
Keywords: 650; adaptive decision-making; aging; child decision-making; development of decision-making; information-board